Arbitrary Polarization Conversion with a Photonic Crystal Slab. Issue 14 (16th January 2019) - Guo, Yu; Xiao, Meng; Zhou, Yang; Fan, Shanhui
Abstract: It is shown that a simple photonic crystal slab structure provides a powerful mechanism for the control of the polarization properties of light. For a lossless system, for a given incident light with any fixed polarization, one can generate arbitrary polarization in the reflected light, as one varies the direction of the incident light. In the lossy system, the capability for arbitrary polarization generation is still preserved for s ‐ or p ‐polarized incident light. This capability for arbitrary polarization generation closely relates to the nontrivial topological properties of the reflection matrix of the structure and exists over a wide range of frequencies. Abstract : A simple photonic crystal slab provides a powerful mechanism for the control of the polarization of light. For a given incident light with any fixed polarization, one can generate arbitrary polarization in the reflected light, by varying the direction of the incident light. Hence the polarization states of the reflected light can cover the entire Poincaré sphere.